Mimetic Magic and Anti-Sacrificial Slayage: A Girardian Reading of Buffy the Vampire Slayer - Dunn, George A. (Mimetic theory and film, 2019)
In the following pages, we defend what might strike some as a surprising thesis, namely, that the view of culture and human relations embedded in the television series Buffy the Vampire Slayer, which ran from 1997 to 2003, coincides with key elements of the theory of mimetic desire and human violence elaborated by René Girard. We first show how one pivotal episode of the series, Season Two’s “Bewitched, Bothered and Bewildered” (2.16), dramatically and metaphorically illustrates key elements of Girard’s theory, after which we will examine the narrative arc of Season Five, showing how the transformation of rivalrous mimesis into positive mimesis and an ethical response to the other is dramatized in the relationship of Buffy Summers to her newly arrived little sister Dawn Summers....